Energy decomposition in molecular complexes implications for the treatment of polarization in molecular simulations - Curutchet, Carles (Journal of computational chemistry, 2003)
Copyright 2003 Wiley Periodicals, Inc. J Comput Chem 24: 1263-1275, 2003